Epidemiological trends of leprosy in an endemic state - Araújo, Kleane Maria da Fonseca Azevedo; Leano, Heloisy Alves de Medeiros; Rodrigues, Rayssa Nogueira; Bueno, Isabela de Caux; Lana, Francisco Carlos Felíx (Rev Rene, 2018)
Objective: to analyze the epidemiological trends of leprosy in an endemic state. Methods:ecological study of temporal trends. The data were taken from the National Disease Notification System and analyzed through a generalized linear regression using the Prais Winsten method. Results: a total of 12,134 new cases of leprosy were analyzed. There was a downward trend of -4.8% in the overall detection rate and of -6.7% in the detection rate in children under 15 years of age. The proportion of new cases of leprosy with grade 2 physical disability at diagnosis showed a stationary trend of 2.7%. It is noteworthy that the trends of epidemiological indicators of leprosy are heterogeneous among the macro-regions of the health system. Conclusion: the incidence of leprosy declined in the general population, in children under 15 years of age, and the proportion of grade 2 disability showed stability. Despite the decline, it is evident that diagnoses occur late and the transmission remains active.